Joint distraction using a purpose-built device for knee osteoarthritis: a prospective 2-year follow-up - Rutger C I van Geenen; Pieter J Emans; Mylène P Jansen; Simon C Mastbergen; Reinoud W Brouwer; Thijmen Struik; Roel J H Custers; Christiaan H W Heusdens; Maarten R Huizinga (RMD Open, 2023)
Objective Knee distraction treatment for end-stage osteoarthritis successfully postpones arthroplasty for years. Studies performed thus far used general intended use, patient-personalised or custom-made devices. In this study, for the first time, a device specifically designed for knee distraction is evaluated.Design 65 patients (≤65 years) with end-stage knee osteoarthritis indicated for arthroplasty received knee distraction. Before, 1-year and 2-year post-treatment, questionnaires were filled out and knee radiographs made. Adverse events and self-reported pain medication were registered.Results Forty-nine patients completed 2-year follow-up: one patient did not complete treatment, three patients received arthroplasty in the first and four patients in the second year follow-up. Eight patients were lost to follow-up in the second year. The total Western Ontario and McMaster Universities Osteoarthritis Index score showed a clinically relevant improvement at 1 and 2 years (+26 and +24 points), as did all subscales (all p<0.001). The minimum radiographic joint space width improved over 1 (+0.5 mm; p<0.001) and 2 (+0.4 mm; p=0.015) years, as did the physical Short-Form 36 (+10 points; p<0.001). The most common adverse event was pin tract infection, experienced by 66% of patients, in 88% successfully treated with oral antibiotics. In two cases, hospitalisation and/or intravenous antibiotics were needed. Eight patients experienced device-related complications. None of the complications influenced 2-year outcomes. Before treatment, 42% of patients used pain medication, which had nearly been halved 1 (23%; p=0.02) and 2 years (29%; p=0.27) post-treatment.Conclusions Patients treated with a general applicable, for knee distraction purpose-built device showed, despite adverse events, significant clinical and structural improvement over 2 years.Trial registration number NL7986.